2015
DOI: 10.17795/icrj-10(03)123
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Health-Related Quality of Life after Coronary Artery Bypass Grafting and Percutaneous Coronary Intervention in Iran via SF-36 and SAQ

Abstract: A B S T R A C TBackground: Cardiovascular Disease (CVD) is one of the major concerns all around the world. It is caused by mass of atherosclerotic plaques in the walls of coronary arteries, which ends in narrowing of veins, heart failure, angina, and Myocardial Infarction (MI). The growing need for therapeutic interventions in CVD patients illustrates the importance of paying special attention to these patients' Quality of Life (QoL) and the vital interventions for their treatment. Objectives: This research ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
1
3
1
Order By: Relevance
“…This finding is an expected outcome from improved emotional wellbeing domain for them. These findings come in line with Fakhrzad, Goudarzi, Barouni, Kojuri, & Jahani., (2016) who reported improved role emotional domain for patients after coronary artery bypass grafting. In addition, Pulimala et al, (2020) reported higher scores in the role emotional domain after CABG.…”
Section: In Relation To Emotional Wellbeing or Mental Health (Mh) Of Quality Of Lifesupporting
confidence: 88%
See 1 more Smart Citation
“…This finding is an expected outcome from improved emotional wellbeing domain for them. These findings come in line with Fakhrzad, Goudarzi, Barouni, Kojuri, & Jahani., (2016) who reported improved role emotional domain for patients after coronary artery bypass grafting. In addition, Pulimala et al, (2020) reported higher scores in the role emotional domain after CABG.…”
Section: In Relation To Emotional Wellbeing or Mental Health (Mh) Of Quality Of Lifesupporting
confidence: 88%
“…Also, this in agreement with Rahman, Flora, Haider, Jahan, & Zafreen., (2018) Who found improved quality in physical component summary (77.4 ±12.37) and psychological component summary (79.88 ±11.03). According to, Ambina, Shalimol, & Anjana., (2019) showed that overall quality of life of post CABG patients 97% had good quality of life with mean score of 69.22 and standard deviation 9.368 and Fakhrzad, Goudarzi, Barouni, Kojuri, & Jahani., (2016) who reported coronary artery bypass grafting led to more improvement in patients' quality of life. Also, this came in congruent with Peric et al, (2017) who reported that more than half of studied patients had improved quality of life.…”
Section: In Relation To Emotional Wellbeing or Mental Health (Mh) Of Quality Of Lifementioning
confidence: 99%
“…In this study, the general, clinical, and psychosocial factors that influence HRQoL in patients who had received PCI were identified. The overall mean HRQoL score in this study of 71.71 was higher than that reported by Fakhrzad et al (2016), which targeted patients who had completed their PCI at least 6 months ago. Jankowska-Polańska et al (2016) reported continuous improvements in HRQoL after PCI.…”
Section: Discussioncontrasting
confidence: 68%
“…The general, medical, and psychological aspects that affect patients' quality of life after receiving PCI were discovered in this research. This research's 71.71 total mean QoL score was greater compared to Fakhrzad et al, (2016), who focused on individuals who had their PCI at least 6 months prior. After PCI, Jankowska-Polaska et al, (2016) noted continual improvement in QoL (Denvir et al, 2006).…”
Section: Discussionmentioning
confidence: 65%